Legal Responsibility of Notaries for Lawsuits Arising from Parties in Ship Sale and Purchase Contracts - Akbar, Muhammad; Witasari, Aryani; Shallman, Shallman (TABELLIUS: Journal of Law, 2026)
Notaries as public officials have the authority to make authentic deeds that serve to provide certainty, order, and legal protection for the parties. Notarial deeds are the basis for the relationship between the parties in making contracts, but lawsuits often arise from the parties due to disputes originating from the deed or the process of making the deed, thus giving rise to issues regarding the notary's legal responsibility. This study aims to analyze the form of notary legal responsibility for the emergence of lawsuits from the parties in ship sale and purchase contracts according to the provisions of law and legislation in Indonesia and the form of legal protection for parties who are harmed due to errors or negligence of the notary in making ship sale and purchase contracts. The research method used is normative legal research with a statutory regulatory approach and a conceptual approach. The data used consists of primary, secondary, and tertiary legal materials analyzed qualitatively. The results of the study show that notaries can be held responsible in civil, administrative and criminal matters in ship sale and purchase contracts depending on the existence of elements of error, negligence or violation of the provisions of laws and regulations, in particular the Civil Code, the Notary Law, Law Number 17 of 2008 concerning Shipping and Regulation of the Minister of Transportation Number 39 of 2017 concerning Registration and Nationality of Ships. Parties who are harmed in a ship sale and purchase contract can obtain legal protection and dispute resolution efforts through litigation, namely filing a lawsuit against a notary in court, and non-litigation channels by conducting negotiations, mediation between the notary and the harmed party, and examinations through the Notary Supervisory Board.